2021
DOI: 10.1007/s10143-021-01664-5
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the COVID-19 pandemic on global neurosurgical education: a systematic review

Abstract: The COVID-19 pandemic has disrupted neurosurgical training worldwide, with the shutdown of academic institutions and the reduction of elective surgical procedures. This impact has disproportionately affected LMICs (lower- and/or middle-income countries), already burdened by a lack of neurosurgical resources. Thus, a systematic review was conducted to examine these challenges and innovations developed to adapt effective teaching and learning for medical students and neurosurgical trainees. A systematic review w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Following relaxed travel limits, residents gradually resumed clinical work but faced challenges: a significant drop in attendance and workload and a shift in working hours during the pandemic. Several studies revealed that workload changes reduced clinical exposure, particularly involving non-critical patients and elective surgeries, hindering residents’ skill development and preparedness for future careers [ 3 , 6 , 19 ]. The impact of COVID-19 on resident working hours varied across hospitals and specialties.…”
Section: Discussionmentioning
confidence: 99%
“…Following relaxed travel limits, residents gradually resumed clinical work but faced challenges: a significant drop in attendance and workload and a shift in working hours during the pandemic. Several studies revealed that workload changes reduced clinical exposure, particularly involving non-critical patients and elective surgeries, hindering residents’ skill development and preparedness for future careers [ 3 , 6 , 19 ]. The impact of COVID-19 on resident working hours varied across hospitals and specialties.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the mode of course delivery, digital course delivery modes were considered. Many synchronous and asynchronous learning resources in medicine and surgery are now available, accelerated by the urgency of the COVID-19 pandemic [35], including the obstetric and paediatric SAFE short courses [36], and some evidence is emerging that a shift to online teaching may improve access for LMIC participants [37]. In the preparatory phase, views.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the mode of course delivery, digital course delivery modes were considered. Many synchronous and asynchronous learning resources in medicine and surgery are now available, accelerated by the urgency of the COVID‐19 pandemic [35], including the obstetric and paediatric SAFE short courses [36], and some evidence is emerging that a shift to online teaching may improve access for LMIC participants [37]. In the preparatory phase, exploratory focus groups described possible barriers for effective online learning including reliable internet connection; cost of mobile data; availability of access devices; difficulty staying engaged; and unfamiliarity.…”
Section: Discussionmentioning
confidence: 99%
“…Foi verificado que a utilização de celulares aumentou, pois, ele também pode ser empregado como um recurso para o ensino remoto: denominado de mobile-learning . Com a pandemia, nos meses de março e abril de 2020, as aulas presenciais foram suspensas no Brasil (SCORSOLINI-COMIN et al, 2020;JAIN et al, 2021). À vista disso, foram adotadas adaptações na rotina, assim como na educação, em que ocorreu a demanda de novas abordagens.…”
Section: Assis Layandraunclassified